Analysis of the rights and duties of insurers in Nigeria (2018)
The paper analyses the rights and duties of Nigerian insurers at common law emanating from the contractual relationship between the insurer and the insured as amplified or abridged under the statute. It argues that the statutory incursion into the common law rules of uberrimae fidei, insurable interest, conditions and warranties and assignment of policies, circumscribing some of the rights exercisable by the insurer against the insured to defeat just claims as well as expanding the scope of the insurer’s duties in order to improve on service delivery is salutary. The paper, however, concludes that further reform measures, aimed at addressing some other salient issues, are still essential in the overall interest of the insuring public.